2004
DOI: 10.1002/anie.200460855
|View full text |Cite
|
Sign up to set email alerts
|

Hemibuckminsterfullerene C30H12: X‐ray Crystal Structures of the Parent Hydrocarbon and of the Two‐Dimensional Organometallic Network {[Rh2(O2CCF3)4]3⋅(C30H12)}

Abstract: Bringing together two C30 hemispheres by coordinating their concave faces to a monometal template or metal cluster represents the first step in an appealing strategy for the controlled synthesis of endohedral fullerene complexes by laboratory methods. A crystalline transition metal complex of this structural type (see picture; Rh blue, O red, C gray; H, F omitted) has now been prepared from hemibuckminsterfullerene C30H12 and [Rh2(O2CCF3)4].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(87 citation statements)
references
References 34 publications
3
84
0
Order By: Relevance
“…3e) reveals that the six hub carbons are pyramidalized to an extent of 9.8° for C1 and 10.8° for C2 (Fig. 3e), both of which are bigger than sumanene (9.0°) 29 , and the latter is comparable to that of hemifullerene C 30 H 12 (10.8°) 31 .…”
Section: Synthesis Of Triazasumanenesmentioning
confidence: 93%
“…3e) reveals that the six hub carbons are pyramidalized to an extent of 9.8° for C1 and 10.8° for C2 (Fig. 3e), both of which are bigger than sumanene (9.0°) 29 , and the latter is comparable to that of hemifullerene C 30 H 12 (10.8°) 31 .…”
Section: Synthesis Of Triazasumanenesmentioning
confidence: 93%
“…These two dispositions resemble the arrangement found in the crystal packing for the homodimers of truxTTF and the related C 30 H 12 , implying a mixture of p-p and CH-p interactions. [30,32] All the optimized heterodimeric structures (1)(2)(3)(4) show close intermolecular contacts in the 2.5-3.7 range ( Figure S1 in the Supporting Information), indicative of stabilizing noncovalent interactions between both bowls.…”
Section: Resultsmentioning
confidence: 99%
“…Accurate calculations of the free energy of complexation suggested that only the staggered conformer in which one dithiole ring is placed inside the bowl These are not the final page numbers! ÞÞ Full Paper 1 1 2 2 3 3 4 4 5 5 6 6 7 7 8 8 9 9 10 10 11 11 12 12 13 13 14 14 15 15 16 16 17 17 18 18 19 19 20 20 21 21 22 22 23 23 24 24 25 25 26 26 27 27 28 28 29 29 30 30 31 31 32 32 33 33 34 34 35 35 36 36 37 37 38 38 39 39 40 40 41 41 42 42 43 43 44 44 45 45 46 46 47 47 48 48 49 49 50 50 51 51 52 52 53 53 54 54 55 55 56 56 57 57 basin could be formed in solution for truxTTF·C 32 32 H 12 , the assignment of the charge-separated state was extremely difficult, but on the basis of earlier findings, its existence is regarded ...…”
Section: Discussionmentioning
confidence: 99%
“…At this point, we want to point out that the degree of pyramidalization should be used with caution to rationalize the reactivity of these PAHs. For instance, the experimental (X-ray crystallography) derived average POAV angles follow the trend: 8.3º (1), [38] 9.6 (2), [7] 9.0º (3), [39] 10.7º (4), [40] 12.1º (5) [41] and 11.6 º (C 60 ), [3] which indicates that cyclopentacorannulene 2 and circumtrindene 5…”
Section: A] Reactant Complex (Rc) Energy: ∆E Rc = E Rc -E(buckybowl) mentioning
confidence: 99%